Water-Guest Interactions Under Clathrate Hydrate Formation Conditions: A Matrix-Isolation Approach. - Vu, Tuan. (2017)
Abstract: The eventual depletion of fossil fuels, coupled with the effects of greenhouse gas emission on the global climate, has called for exploration of alternative technologies to address increasing energy demand. Clathrate hydrates, crystalline solids composed of gas and water, is a class of materials with enormous potential both as an energy source and as a medium for gas storage. These peculiar compounds occur naturally in the permafrost and the deep oceans, and are estimated to contain more carbon than all the oil found on Earth. There have been numerous investigations on the kinetics and thermodynamics of clathrate formation; however, a molecular-level understanding of this phenomenon is far from complete. A major challenge has been characterization of the water-guest interactions at the beginning stages of nucleation. Infrared spectroscopy is among the most sensitive probes for detecting interactions involving water, but it is rarely chosen for hydrate studies due to the high absorbance of bulk aqueous samples. This work employs a room-temperature matrix isolation technique to circumvent the opacity problem. Carbon tetrachloride is used as the solvent to disperse water into isolated monomers with ambient thermal energies, providing an excellent environment to investigate interactions with hydrate guest molecules at typical clathrate formation conditions (temperatures near 0 oC and pressures between 1-55 atm). Propane is one of the simplest hydrocarbons that form a stable clathrate hydrate under relatively mild conditions. In carbon tetrachloride, the water monomer signature consists of the symmetric stretch, the asymmetric stretch, and rotational wings associated with the asymmetric stretch. Interaction of water with propane causes a dangling OH (d-OH) peak to appear between the symmetric and asymmetric stretches, indicating a guest-induced water cluster. A combination of isotopic substitution and density functional theory calculations has established the presence of an attractive interaction between the methylene groups of propane and the electron lone pairs of water. Aside from their potential role in energy applications, hydrate plugs formed during transportation and processing of natural gases have been a longstanding nuisance for the petroleum industry. A number of thermodynamic inhibitors, primarily methanol, have been used to prevent hydrate formation in natural gas pipelines for many years, but their interactions with the hydrate constituents are not very well identified. Matrix-isolation experiments are hence performed to elucidate the mutual interactions between methanol, water and propane in CCl4. Experimental data indicate that while methanol forms hydrogen bond to water via donation of the hydroxyl group (binding constant K = 4.4 x 102), it does not have any specific interaction with propane. These results are consistent with a picture in which methanol disrupts formation of the water-guest complex by competing with propane for the oxygen lone pairs in water. Interactions between water and pentacyclic guests such as tetrahydrofuran (THF) and cyclopentane are subsequently examined. Despite the distinct difference in aqueous solubilities (THF is totally miscible with water and cyclopentane is hydrophobic), both compounds form stable clathrates above 0 oC at ambient pressure. Knowledge of the nature of the water structure surrounding the cyclic guests is thus a critical component for a deeper understanding of the nucleation mechanism. Experimental results show that compared to propane, cyclopentane gathers significantly larger clusters of water in carbon tetrachloride. The presence of a bridging water molecule is also observed for the cyclopentane-water cluster, providing compelling evidence for arrangement of water molecules in a local five-membered ring motif. The rigidity of the cyclic guest in this instance partially immobilizes water molecules in its vicinity, and reduces the entropic cost for forming a complete hydrate lattice.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Chemistry.; Advisor: Mary Jane Shultz.; Committee: Elena Rybak-Akimova, Arthur Utz, and Thomas Keyes.; Keyword: Physical chemistry.